PENGARUH MOTIVASI DAN KOMITMEN TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA MAHASISWA DI UNIVERSITAS NUSA PUTRA) - Muhamad Ikbal Robani (STKIP Subang, 2026)
This study aims to analyze the influence of motivation and work commitment on student employee performance at Nusa Putra University. Working students have dual roles as both students and employees, requiring them to maintain a balance between academic and professional responsibilities. This situation makes motivation and work commitment important factors that can influence performance. This study used a quantitative approach with a survey method. Data were collected through questionnaires distributed to actively working students and analyzed using multiple linear regression. The results indicate that motivation has a positive and significant effect on student employee performance. Furthermore, work commitment also has a positive and significant effect on performance. Simultaneously, motivation and work commitment contribute significantly to improving student employee performance. These findings support human resource management theory, which states that internal drive and commitment to work play a crucial role in increasing productivity. This research is expected to provide practical implications for educational institutions and workplaces in creating an environment that supports student-employee role balance